Mechanical thrombectomy for large ischemic stroke: a critical appraisal of evidence from 6 randomized controlled trials - Sarraj, Amrou; Yoshimura, Shinichi; Thomalla, Götz; Huo, Xiaochuan; Arquizan, Caroline; Yoo, Albert J.; Morimoto, Takeshi; Bendszus, Martin; Lapergue, Bertrand; Nguyen, Thanh N.; Campbell, Bruce C.V.; Costalat, Vincent; et al. (Stroke, 2025)
Recently, 6 randomized trials evaluated the efficacy and safety of endovascular thrombectomy in patients with large core stroke. This review examines the differences in clinical and imaging eligibility and their impact on the interpretation of evidence and potential neuroimaging workflow. Pending results of a planned patient-level meta-analysis, it also evaluates clinical outcomes and thrombectomy treatment effect across those trials, overall and within selected clinical and imaging subgroups most relevant to clinical practice. Additionally, the implications of extending thrombectomy eligibility to patients with large core stroke on stroke systems of care and societal benefits are discussed.